Development of a Smart Grid Simulation Environment, Part II: Implementation of the Advanced Distribution Management System - Leite, Jônatas Boás [UNESP]; Mantovani, José Roberto Sanches [UNESP] (Springer Nature, 2014)
A smart grid is an electric power system with high levels of automation, dispersed generation, intelligent monitoring, and control; however, because the distribution networks in operation today do not have these characteristics, studies concerning the control, planning, and operation of the smart grid are difficult to perform. To overcome these practical difficulties, studies investigating the smart grid can be conducted in computational environments that are able to reproduce meticulously the electrical and communicational behaviors expected by the smart grid. Therefore, in this paper, the development of a platform to simulate the advanced distribution management system (DMS) from a reference model for smart grid, which has seven layers, is proposed. Part II of this paper refers to the four upper layers. First, it describes the system layer architecture where all computational hardware is virtualized to create the smart grid simulation environment. Subsequently, the three logical layers, Model, Analysis, and Intelligence, are considered in the construction of the advanced DMS supervisor. The uses of some applications of the supervisor are shown to reveal their potential.
Keywords: Advanced distribution management system (DMS); Smart grid; Supervisor; Virtualization